Cold storage [compact disc, unabridged] : a novel - Koepp, David (Harper Audio, 2019)
"When Pentagon bioterror operative Roberto Diaz was sent to investigate a suspected biochemical attack, he found something far worse: a highly mutative organism capable of extinction-level destruction. He contained it and buried it in cold storage deep beneath a little-used military repository. Now, after decades of decaying in a forgotten sub-basement, the specimen has found its way out and is on a lethal feeding frenzy. Only Diaz knows how to stop it. He races across the country to help two unwitting security guards--one an ex-con, the other a single mother. Over one harrowing night, the unlikely trio must figure out how to quarantine this horror again. All they have is luck, fearlessness, and a mordant sense of humor. Is that enough, to save all of humanity?"--Container.